Progress in the Diagnosis and Classification of Pituitary Adenomas - Syro, Luis V.; Rotondo, Fabio; Ramirez, Alex; Di Ieva, Antonio; Sav, Murat Aydin; Restrepo, Lina M.; Serna, Carlos A.; Kovacs, Kalman (Frontiers in Endocrinology, 2015)
Pituitary adenomas are common neoplasms. Their classification is based upon size, invasion of adjacent structures, sporadic or familial cases, biochemical activity, clinical manifestations, morphological characteristics, response to treatment and recurrence. Although they are considered benign tumors, some of them are difficult to treat due to their tendency to recur, despite standardized treatment. Functional tumors present other challenges for normalizing their biochemical activity. Novel approaches for early diagnosis as well as different perspectives on classification may help to identify subgroups of patients with similar characteristics, creating opportunities to match each patient with the best personalized treatment option. In this paper we present the progress in the diagnosis and classification of different subgroups of patients with pituitary tumors that may be managed with specific considerations according to their tumor subtype.